Niraparib for the treatment of metastatic ccRCC in a patient with CDK12 and RAD51C mutations: a case report - Yue, Xiaolong; Yang, Chenkang; Cao, Dandan; Li, Yue (Frontiers in Pharmacology, 2024)
Background: Niraparib, a poly ADP-ribose polymerase inhibitors (PARPi), has been widely applied in the intervention of epithelial ovarian, fallopian tube, or primary peritoneal cancer.Nevertheless, as of the present moment, there are limited instances demonstrating favorable outcomes stemming from niraparib therapy in patients with clear cell renal cell carcinoma (ccRCC).Case presentation: Here, we report a case of a 50-year-old patient with ccRCC who subsequently developed distant metastasis. The patient received monotherapy with pazopanib and combination therapy with axitinib and tislelizumab, demonstrating limited efficacy. Liquid biopsy revealed missense mutations in the CDK12 and RAD51C of the homologous recombination repair (HRR) pathway, suggesting potential sensitivity to PARPi. Following niraparib treatment, the patient's condition improved, with no significant side effects.In summary, patients with ccRCC harboring HRR pathway gene mutation may potentially benefit from niraparib. This will present more options for ccRCC patients with limited response to conventional treatments.